Anomaly detection in netflow traffic: workflow for dataset preparation and analysis - Roponena, Evita; Poļaka, Inese; Grabis, Ja¯ nis (Frontiers in Computer Science, 2025)
Information and communication technology (ICT) is crucial for maintaining efficient communications, enhancing processes, and enabling digital transformation. As ICT becomes increasingly significant in our everyday lives, ensuring its security is crucial for maintaining digital trust and resilience against evolving cyber threats. These technologies generate a large amount of data that should be analyzed simultaneously to detect threats to an ICT system and protect the sensitive information it may contain. NetFlow is a network protocol that can be used to monitor network traffic, collect Internet Protocol (IP) addresses, and detect anomalies in NetFlow. The article follows the design science research (DSR) methodology to reach an objective of providing a methods for developing a set of features for NetFlow analysis with a machine learning. The sets of features were analyzed and validated by implementing anomaly detection with the K-means clustering algorithm and time-series forecasting using the long short-term memory (LSTM) method. The study provides two separate sets of features for both machine learning methods (24 features for clustering and 14 for LSTM), an overview of the anomaly detection methods used in this research and a method to combine both machine learning approaches. Furthermore, this study introduces a method that integrates the outputs of both models and evaluates the reliability of the final decision based on Bayes' theorem and previous performance of the models.